Monitoring Kinerja Penyelenggaraan Izin Usaha Apotek di Dinas Kesehatan Kota Pekanbaru - Hendry Andry; Milandry, Anggraini Dwi; Afrizal (UIR Press, 2025)
This research aims to determine and describe the performance monitoring of the Pekanbaru City Health Office regarding the issuance of business permits for business actors who wish to or have already established a pharmacy. The urgency of this research is because field data shows that there are still many pharmacies in Pekanbaru that are operating but do not have business licenses. The author uses William Dunn's monitoring function concept to analyze the performance monitoring of the Pekanbaru City Health Office regarding the operation of pharmacy business permits, specifically the compliance, auditing, explanation, and accounting indicators. This research was conducted at the Pekanbaru City Health Department using a descriptive-qualitative research type and method, so the data obtained will be analyzed qualitatively and discussed descriptively. Monitoring the performance of the Pekanbaru City Health Office regarding the issuance of pharmacy permits is quite well implemented because the research results for the compliance indicator have been met and the explanation indicator is quite well implemented. Meanwhile, the auditing indicator has not been implemented as it should be, and the accounting indicator has also not been implemented.